Gestión del valor en la comercializadora Representaciones SAS - Guarnizo García, María Camila; Moreno Bravo, Sebastian (Universidad Antonio Nariño, 2023)
The research was carried out in the company Comercializadora Representaciones SAS with the purpose of measuring the economic performance and efficient development of operational activities for the years 2019-2021, through the application of analysis tools and the EVA factor, it is possible to identify the successes or failures of the business strategy and that evidence the management in the generation of value for investors; The type of research was descriptive with a quantitative approach where the application of financial analysis instruments is achieved to comply with the proposed objectives, managing to show that the operational activities during this period of time effectively contributed to improve their financial performance.